2011
DOI: 10.1183/09031936.00193809
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for epidemiological studies on COPD

Abstract: The prevalence of chronic obstructive pulmonary disease (COPD) has been extensively studied, especially in Western Europe and North America. Few of these data are directly comparable because of differences between the surveys regarding composition of study populations, diagnostic criteria of the disease and definitions of the risk factors. Few community studies have examined phenotypes of COPD and included other ways of characterising the disease beyond that of spirometry.The objective of the present Task Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 140 publications
(139 reference statements)
2
52
0
1
Order By: Relevance
“…52 A further strength of our study was the wide range of clinically relevant conditions examined in the context of disease staging, with higher prevalence of respiratory symptoms, respiratory and cardiovascular diseases, breathlessness and poor self-rated health among participants in the tightest definitions of FT and LLN obstruction, confirming similar findings in the USA 5354 While recent guidelines13 46 55 recommend adopting multidimensional definitions of respiratory disease, our study outcomes were defined only using spirometry. While we acknowledge the merits of a multidimensional approach, and agree that neither spirometric cut-off is able to fully characterise the complex diagnostic features of COPD,56 our primary aim was to use up-to-date survey data to evaluate differences in prevalence according to FT and LLN thresholds, to provide baseline data for monitoring purposes in the UK, and promote comparability with international studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…52 A further strength of our study was the wide range of clinically relevant conditions examined in the context of disease staging, with higher prevalence of respiratory symptoms, respiratory and cardiovascular diseases, breathlessness and poor self-rated health among participants in the tightest definitions of FT and LLN obstruction, confirming similar findings in the USA 5354 While recent guidelines13 46 55 recommend adopting multidimensional definitions of respiratory disease, our study outcomes were defined only using spirometry. While we acknowledge the merits of a multidimensional approach, and agree that neither spirometric cut-off is able to fully characterise the complex diagnostic features of COPD,56 our primary aim was to use up-to-date survey data to evaluate differences in prevalence according to FT and LLN thresholds, to provide baseline data for monitoring purposes in the UK, and promote comparability with international studies.…”
Section: Discussionsupporting
confidence: 68%
“…Analysis of the National Health and Nutrition Examination Survey (NHANES) 2007–2010 showed that FT and LLN prevalence estimates among US adults aged 40–79 years decreased, in relative terms, by approximately one-third after administration of bronchodilators 45. Although recent guidelines from NICE46 and ERS13 recommend use of postbronchodilator spirometry to confirm the presence of airflow obstruction, debate continues over its use in epidemiological settings, with the arguments against including ethical issues such as possible side effects and contraindications 47. Potential misclassification of disease status through bronchodilators not being used was reduced by excluding participants with physician-diagnosed asthma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Global Initiative on Obstructive Lung Disease (GOLD) a post-bronchodilator ratio < 0.7 is defined as not fully reversible airway obstruction [10]. The ERS and American Thoracic Society (ATS) recommend the use of Lower Limit of Normal (LLN) defined as the lower fifth percentile of the distribution for healthy non-smokers to define an abnormally low ratio [11-13]. The LLN definition is dependent on the set of reference values in use.…”
Section: Introductionmentioning
confidence: 99%
“…24 The ERS Task Force has recently recommended using post-bronchodilator LLN values to define COPD. 25 In addition, the LLN criterion depends on reliable reference values derived from the healthy local population; many countries don't have their own reference values for spirometry, and even if they do, they are in all likelihood based on values obtained from asymptomatic never-smokers. In populations such as the Asia Pacific region, where smoking is not the overwhelming cause of COPD, the 'apparently healthy population' may include many who suffer from asymptomatic undiagnosed airflow limitation due to factors other than tobacco smoking, which may lead to significant underdiagnosis of true COPD in these population studies.…”
mentioning
confidence: 99%